2008
DOI: 10.1016/j.trsl.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine-positive erythrocytes bind to immobilized and soluble thrombospondin-1 via its heparin-binding domain

Abstract: Phosphatidylserine (PS)-dependent erythrocyte adhesion to endothelium and sub-endothelial matrix components is mediated in part via thrombospondin (TSP). While TSP exhibits multiple cell-binding domains, the PS-binding site on TSP is unknown. Since a cell-binding domain for anionic heparin is located at the amino-terminus, we hypothesized that PS-positive red cells (PS +ve -RBCs) bind to this domain. We demonstrate that both heparin and its low-molecular-weight derivative enoxaparin (0.5-50u/ml) inhibited PS +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Thrombospondin A had the lowest dissociation constant. Similar Kd values for heparinoids have been documented elsewhere (Koenig et al , ; Barabino et al , ; Wang et al , ; Wang & Geng, ; Brittain et al , ; Simonis et al , ; Gayen Betal & Setty, ).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Thrombospondin A had the lowest dissociation constant. Similar Kd values for heparinoids have been documented elsewhere (Koenig et al , ; Barabino et al , ; Wang et al , ; Wang & Geng, ; Brittain et al , ; Simonis et al , ; Gayen Betal & Setty, ).…”
Section: Resultssupporting
confidence: 82%
“…Several non‐membrane bound proteins, such as von Willebrand factor (VWF) (Krishnan et al , ; Zhou et al , ; Chen et al , ) and thrombospondin (TSP) (Brittain et al , , ,b; Novelli et al , ), may contribute by serving as anchoring or bridging proteins, and several of these proteins have heparin‐binding sites. Furthermore, both heparin and low molecular weight heparins (LMWHs) can bind to several adhesion proteins (Koenig et al , ; Gupta et al , ; Polanowska‐Grabowska et al , ; Burnette et al , ) to inhibit SS‐RBC adhesion (Barabino et al , ; Matsui et al , , ; Gayen Betal & Setty, ) and to restore blood flow in animal models of SCD (Embury et al , ).…”
mentioning
confidence: 99%
“…A double blind randomized trial with tinzaparin in SCD patients during acute VOCs has documented a reduction of severity and duration of the VOCs51,60.…”
Section: Anti-adherence Therapy In Sickle Cell Diseasementioning
confidence: 99%
“…Endothelial cell PS receptor expression is upregulated in response to inflammatory cytokines, hypoxia, and free hemoglobin . Erythrocyte PS also binds to thrombospondin, a protein that is present in subendothelial matrix . The importance of PS in normal hemostasis is illustrated by Scott syndrome.…”
Section: The Pathophysiology Of Thrombosis In Imhamentioning
confidence: 99%
“…In addition, in vitro studies using RBCs taken from people with sickle cell disease have shown that PS binds to the heparin‐binding domain of the endothelial cell matrix protein, thrombospondin. Clinically relevant doses of heparin inhibit this binding in a concentration‐dependent manner . Heparin also inhibits complement.…”
Section: Thromboprophylaxis In Imhamentioning
confidence: 99%